2022
DOI: 10.1088/1361-6587/ac93b0
|View full text |Cite
|
Sign up to set email alerts
|

Theory of mean E × B shear in a stochastic magnetic field: ambipolarity breaking and radial current

Abstract: The mean E×B shear in a stochastic magnetic field is calculated, using the radial force balance relation and transport equations. This analysis is relevant to the L→H transition with resonant magnetic perturbations (RMP), and special focus is placed upon the physics of non-ambipolar transport and radial current. The key physical process is the flow of fluctuating current along wandering magnetic fields. The increments in poloidal and toroidal rotation, density and ion pressure are calculated. The radial envelo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…Since the electrons thermal velocities are much faster than massive ions, the loss of electrons along the disturbed magnetic field lines is much more than ions, which charges the plasma edge positively. Recent comprehensive theoretical investigation gives a detailed physical process in which the stochastic RMP driven magnetic fields produce a radial electron current density, which drives particle transport [23]. We now try to find experimental evidence to verify this explanation.…”
Section: Impact Of Rmp On Poloidal Flowmentioning
confidence: 78%
“…Since the electrons thermal velocities are much faster than massive ions, the loss of electrons along the disturbed magnetic field lines is much more than ions, which charges the plasma edge positively. Recent comprehensive theoretical investigation gives a detailed physical process in which the stochastic RMP driven magnetic fields produce a radial electron current density, which drives particle transport [23]. We now try to find experimental evidence to verify this explanation.…”
Section: Impact Of Rmp On Poloidal Flowmentioning
confidence: 78%
“…(i) One may notice that zonal flow, a critical player in L-H transition, is missing from our model. In fact, it has been found that the stochastic magnetic field can indeed affect the zonal flow and the radial electric field [8,55]. Many phenomena in RMP experiments, such the increase in the L-H transition power threshold, can be attributed to the weakening of the shear flow.…”
Section: Suggested Experiments and Future Planmentioning
confidence: 99%
“…However, as turbulence evolution and transport bifurcation now happen in a background stochastic field, an increase in the L-H transition power threshold has been observed on multiple machines [4][5][6]. To get insight into the tripartite trade-off among confinement, heating power, and boundary control, models of turbulence dynamics [7], zonal flow evolution [8], and L-H transition [9] have been reformulated in the presence of extrinsic stochasticity. All these theories are either based on or closely relevant to a fundamental question: how does an ambient stochastic magnetic field modify plasma turbulence and the underlying instability process?…”
Section: Introductionmentioning
confidence: 99%